EVALUATION OF ELECTRIC CAR RESEARCH TRENDS THROUGH BIBLIOMETRIC ANALYSIS: A Literature Review - Lazuardy, Ardhy (Asosiasi Dosen Muda Indonesia, 2023)
Due to increasing environmental and sustainability concerns, electric cars have become a significant research focus in recent years. To understand the development and Impact of scientific research related to electric vehicles, a bibliometric analysis was carried out. This research collects data from Scopus, using the keywords